A comparative experiment investigate of strength parameters for Longmaxi shale at the macro- and mesoscales. (3rd August 2017) - Dong, Guangjian; Chen, Ping
Abstract: The strength parameters of rock is important to the storage and development of hydrogen gas and natural gas. The rock strength parameters is the basis of the establishment of storage space and wellbore, especially for the shale formation. However, the strength parameters and indentation mechanism of shale are unclear. It is necessary to research the strength parameters and dynamic indentation of shale from the multiscale perspective. A comparative experimental study of shale indentation at the macro- and mesoscales was conducted. The experimental investigate determined the four stages of shale indentation at the mesoscale. With increasing loading rate at the same load value, indentation depth decreases, and the critical fracture load of shale increases. The result shows that the indentation load can improve the rate of penetration, but the shale strength increases slightly at the same time, which suppresses the energy release of the shale fragmentation. The probability of indentation fragmentation occurs 2–3 times at the mesoscales is greater than 4 times the value at the macroscale. The macro averages of shale hardness and elastic modulus are close to the mesoscale values. The differences are 7% and 5.5%, respectively. The study results can be used in the storage and development of hydrogen gas and the optimization design of drilling tools. Highlights: Experimental study of strength parameters of shale at the macro- and mesoscales was carried out. Comparative analysis of macro- and meso-experimental results of shale strength parameters was provided. The effects of loading rate, indentation depth and repeat indentation on shale were studied.